Bimbingan Dan Pelatihan Menjadi Khatib Dalam Menumbuhkan Kemampuan Menyusun Dan Menyampaikan Khutbah Di Kecamatan Jambu, Kabupaten Semarang - Muhyiddin, Ahmad Shofi; Bastomi, Hasan; Labibah, Ana Niswatul (Community Development: Jurnal Pengembangan Masyarakat Islam, 2025)
Guidance And Training To Become A Khatib In Developing The Ability To Compile And Delivery Sermons In Jambu District, Semarang Regency. This community service activity aims to improve the ability of preachers to compose and deliver structured, relevant, and communicative sermons in Jambu District, Semarang Regency. The method used is the Asset-Based Community Development (ABCD) approach, which focuses on identifying and utilizing local assets such as religious leaders, mosque networks, and da'wah traditions. The activity was carried out through five stages: Discovery, Dream, Design, Define, and Destiny, involving active community participation. The results showed significant improvements in the structure of sermons, the relevance of themes to social issues, and the public communication skills of participants. The implication of this activity is the formation of a local preacher community capable of strengthening the function of mosques as centers for community development and agents of social change. Recommendations from this activity include the need for further mentoring, the development of contextual training modules, and institutional support from the government and religious institutions for program replication in other areas. The ABCD approach has proven effective in building a sense of ownership and sustainability of the community-based preacher training program.